Christmas in Whispering Pines [large type] - Dunn, Scarlett (Dunn, Scarlett. Langtry sisters trilogy., 2018)
"On the heels of her blowout European tour, opera star Emma Langtry has returned home to Whispering Pines to spend time with her family. But she isn't alone: a smitten French prince has followed her, determined to win her love. While Emma enjoys his company, marriage isn't on her agenda. Then she meets the mysterious Clay Hunt . . . Clay is the new pastor in Whispering Pines. Years ago, after a shattering loss, he left everything behind--including his faith--to seek revenge. Tormented by his actions, he's now resolved to earn redemption, and has devoted himself to his parishioners. He believes he has nothing to give any woman, not even one as enticing and headstrong as Emma Langtry. But when the Langtry sisters' outlaw brother turns up, bringing danger in his wake, fate will bring Emma and Clay together--and once that happens, nothing will be able to tear them apart"--